2019
DOI: 10.1016/j.sjbs.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroacupuncture on mice model of permenopausal depressive disorder

Abstract: ObjectiveStudy the effect of electroacupuncture on permenopausal depressive disorder (PDD) model through the peri-menopausal depression model mice.MethodsKM female mice were selected. Except for the blank group (BG), the other groups of mice were removed by castration method. The mice of PDD was prepared by combining chronic unpredictable stimulation. Mice in the model group (MG) were not treated and fed normally. The western medicine group (WG) was given the corresponding drug for treatment. The electroacupun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…Based on the PMD mouse model, Guo and colleagues reported EA significantly reduced mice's depressed performance, reflected by decreased time of forced swimming and tail suspension, increased number of spontaneous activities, etc. They also observed increased 5-HT, NE, and DA in mice's cerebral tissue, as well as increased serum E2 and decreased serum FSH and LH (72). However, in our review, the changes in those hormones in the acupuncture group did not differ from those in antidepressant/antidepressant + HRT group.…”
Section: Interpretation Of Findingscontrasting
confidence: 50%
“…Based on the PMD mouse model, Guo and colleagues reported EA significantly reduced mice's depressed performance, reflected by decreased time of forced swimming and tail suspension, increased number of spontaneous activities, etc. They also observed increased 5-HT, NE, and DA in mice's cerebral tissue, as well as increased serum E2 and decreased serum FSH and LH (72). However, in our review, the changes in those hormones in the acupuncture group did not differ from those in antidepressant/antidepressant + HRT group.…”
Section: Interpretation Of Findingscontrasting
confidence: 50%
“…[ 3 ] It can effectively improve systemic physical symptoms such as poor digestion and insomnia through its overall regulatory effect. Acupuncture can effectively improve depressive symptoms compared with control acupuncture, [ 4 ] and it may play a unique role in the antidepressant mechanism. Animal experiments also showed that learning, memory, and depressive behaviors of rat samples improved considerably after EA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical observation, some researchers have noticed that the long-term follow-up investigation effect of acupuncture was similar to that of antidepressants alone, without meaningful improvement for depression patients. [ 4 6 ] But when patients were treated with acupuncture and antidepressants, the effect could be maintained for a longer time. [ 7 ] Aiming to answer this question, we should consider from a macro perspective, and explore the mechanical differences between the use of acupuncture with antidepressants in the treatment of depression compared with antidepressants alone.…”
Section: Introductionmentioning
confidence: 99%
“…EA also had this effect. Guo et al (2019) showed that EA at GV20, BL23, and SP6 could improve the activity and memory of PDD mice, improve sex hormone disorders in serum (elevated T and E2, FSH and LH decreased), increase the levels of monoamine transmitters (5-HT, NE, DA) in brain tissue, and improve the morphological changes of the hypothalamus. Lee et al (2019) found that acupuncture at KI10, LR8, LU8, and LR4 alleviated depressive-like behaviors in CRS mice by regulating the hippocampus, cingulate cortex, motor cortex, and thalamus activity (considered as the specific area where acupuncture works).…”
Section: Background Role Of Acupuncture In Mddmentioning
confidence: 99%